Faktor-Faktor yang Mempengaruhi Kesiapan Berwirausaha - Estu Niana Syamiya; Disman Disman; Suwatno Suwatno; Hari Mulyadi (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2023)
Results of this research analysis, measure and find out about the Entrepreneurial Readiness of Aliyah students at MA Pesantren Tei-Multazam through influencing factors using 5 independent variables (personality perception, motivation, education, family, personal desires). The data used in this research is primary data obtained from questionnaires distributed to female students at the Aliyah madrasah school at the Tei-Multzam Islamic boarding school. This study had a population of 145 female students and a sample of 106 female students. The sampling technique in this research is Probability Sampling. Data collection was carried out using a questionnaire, distribution of questionnaires using a questionnaire. Data analysis in this research uses Multiple Linear Regression Analysis. The instruments distributed to the sample have been tested for validity and reliability. The results of this research show that: 1) Personality Perceptions influence entrepreneurial readiness, 2) Motivation has no influence on entrepreneurial readiness, 3) Education influences entrepreneurial readiness, 4) Personal desires influence entrepreneurial readiness and 5) Personal desires influence entrepreneurial readiness. The results of the implications of this research are 1) Personality perceptions have implications for entrepreneurial readiness, 2) Motivation has no implications for entrepreneurial readiness, 3) Education has implications for entrepreneurial readiness, 4) Personal desires have implications for entrepreneurial readiness, and 5) Personal desires have implications for entrepreneurial readiness